Crises of Education Strategies in Community Empowerment Programs (A Case Study in Setu Patok, Cirebon) - Farida Farida (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2017)
Community empowerment emerges to be a keyword in Indonesian government programs for alleviating poverty and promoting development. Empowerment is defined as a process to realize the ability and enhance manpower to act and reason. Therefore, there is always a process of learning that is recognized as education. According to the Law Number 20 of 2003 on National Education System, the government holds education through three education models, namely: formal, non-formal, and informal education. This present study aims to analyze aspects of education in the context of community empowerment programs organized by the government in Karangdawa, Setu Patok, Mundu Sub-district, Cirebon Regency. The theory of strategy proposed by Henry Mintsberg was employed in this study. This theory highlights five aspects for exploring the strategies of education in terms of community empowerment, including plans, ploys, patterns, positions, and perspectives. The research findings reveal that the managed education strategies were categorized into the low level in relation to the plan, ploy, pattern, position, and perspective strategies. The planning of educational activities were carried out by using a top-down approach. This approach demonstrated inflexible patterns in working, did not involve a community as a group target in all the education models. Likewise, the government agencies, playing the role as the agents of education programs, worked individually focusing on their own targets without coordinating for considering the attainment of each program in terms of the community empowerment in a certain area. Based on the position and perspective strategies, the government was very low to deem both internal and external situations as a result of the government’s paradigm in viewing the community empowerment that was merely human-oriented.